2020
DOI: 10.1016/j.anbehav.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between social groups of colobus monkeys (Colobus vellerosus) explain similarities in their gut microbiomes

Abstract: Interactions between social groups of colobus monkeys (Colobus vellerosus) explain similarities in their gut microbiomes

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 91 publications
2
42
2
Order By: Relevance
“…This result is consistent with social microbiome theory (Grieneisen et al, 2017;Sarkar et al, 2020) and gray wolf social ecology (Mech & Boitani, 2003;Stahler et al, 2020), as pack members cooperatively share territory, prey, social contacts, and microbes. Similar patterns have been observed in cohabitating humans (Dill-McFarland et al, 2019;Song et al, 2013) and nonhuman mammals (Goodfellow et al, 2019;Leclaire et al, 2014;Wikberg et al, 2020) with varying degrees of relatedness.…”
Section: Discussionsupporting
confidence: 74%
“…This result is consistent with social microbiome theory (Grieneisen et al, 2017;Sarkar et al, 2020) and gray wolf social ecology (Mech & Boitani, 2003;Stahler et al, 2020), as pack members cooperatively share territory, prey, social contacts, and microbes. Similar patterns have been observed in cohabitating humans (Dill-McFarland et al, 2019;Song et al, 2013) and nonhuman mammals (Goodfellow et al, 2019;Leclaire et al, 2014;Wikberg et al, 2020) with varying degrees of relatedness.…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies have shown that the social environment can strongly affect gut microbiota composition in group-living species, such as primates living in large groups [ 26 , 29 ] or smaller family units [ 27 , 28 , 30 ]. Here, we provide the first evidence for similar effects in a non-group-living species.…”
Section: Discussionmentioning
confidence: 99%
“…In highly social group-living mammals, the host social environment seems to have important effects on the gut microbiota. Social group membership has been shown to predict gut microbiota composition in several species of primates [26][27][28][29][30][31] and other group-living mammals [32][33][34]. Social group effects also occur in humans, as unrelated individuals living in the same household were found to have a more similar microbiota than relatives living in different households [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of high-throughput sequencing technologies, in combination with the development of effective, non-invasive sampling techniques, has resulted in a recent proliferation of studies investigating the GM of wild animals. Several studies have demonstrated interspecific differences in GM characteristics [17][18][19], and also variation between groups [20][21][22] or individuals [23][24][25] within the same natural population. Most of these studies have focussed on investigating the drivers of intraspecific variation in the bacterial component of the GM, identifying a suite of environmental factors that can influence this, including habitat quality and dietary differences [24][25][26], as well as host-related traits, such as age, sex, and host genotype [23,27,28].…”
Section: Introductionmentioning
confidence: 99%